2018
DOI: 10.1177/2325967118779854
|View full text |Cite
|
Sign up to set email alerts
|

Hurt on the Hill: A Longitudinal Analysis of Obstacle Course Racing Injuries

Abstract: Background:Obstacle course racing (OCR) has become a popular sport in recent years as it challenges participants’ mental and physical endurance through a combination of trail running and obstacles. There is currently only a limited amount of published work reporting injury types or rates at these events.Purpose:This study aims to build on the current literature, analyzing injury rates and patterns at OCR events.Methods:A secondary data analysis of deidentified medical charts from 33 OCR events in Canada from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Such excessive physical activity may lead to overuse injuries [20]. In ultra-endurance events, overuse injuries may arise from overtraining or from injury during the event [12,19,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such excessive physical activity may lead to overuse injuries [20]. In ultra-endurance events, overuse injuries may arise from overtraining or from injury during the event [12,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Today, obstacle courses have been integrated into racing formats, and the physical and mental demands placed upon participants can be significant [12]. Rabb and Coleby [12] reported that medical personnel at OCR events should anticipate up to a 5% injury rate, with 4.5% requiring emergency department treatment. Such injuries occur due to environmental (e.g., weather, type of obstacle, apparel malfunctions) and physical conditions (e.g., hydration, mental/physical fatigue).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the season injury rate illustrates the cumulative injury rate occurring over one year, obtained by dividing the total injury rates within a year by 12 months. 51 A higher injury rate indicates a greater frequency of injuries relative to the population or exposure, while a lower rate suggests a lower incidence of injuries.…”
Section: Assessment Of In-event Health Servicesmentioning
confidence: 99%